QSPM Usage in SWOT Analysis as a Tool for Strategic Management of Caspian Sea Coasts (Case Study: Tourism Development in Caspian Eastern Coast at Gilan Province) - Nejad, Mohammad Ali Rahimipour Sheykhani; Agha, Farzaneh Nasiri Jan; Zadeh, Yalda Fattah (Journal of Tourism Management Research, 2017)
The studied area is located in the eastern coast of Caspian Sea at the Gilan province in Iran including the sea shores at Rudsar, Langaroud, Lahijan, and Astane Ashrafiyeh cities. This research aims to study and analyze the important factors on developing tourism industry in the selected area. Therefore, the influential capabilities that lead to growth of potential tourists and tourism in the coasts, and have positive impacts on the economy and job growth of the area have been evaluated; the current weak points are discussed as well. This research employed field operation, observation, interview, survey and opinions of experts for data collection and analysis of the current situation in this area. Results show that to improve the tourism industry in the eastern coast of Caspian sea, the current coast-relevant proposals have to be integrated with other tourism factors applicable in the sea coasts; such as linking the sea and mountain, enhancing the cooperation of local people, increasing the number of secured sites, increasing the number of lifeguards, providing utility services in the research area, equipping the infrastructures specially accessibility and transportation, health and security, education and information. At the end, strategic suggestion are provided.